2021
DOI: 10.1108/ijefm-02-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in agricultural and county shows: conceptualising the e-eventscape

Abstract: PurposeIn response to the cancellation of a host of events during the summer of 2020, the purpose of this paper is to examine the rapid innovation that created an online County Show. County Shows are traditionally associated with agriculture and the wider rural economy of a region and provide a range of visitor experiences alongside business networking and trading opportunities. The case of the online Lincolnshire Show sought to replicate many aspects of a physical show, and this paper evaluates its effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Reliant on immigrant labor and overseas markets, the impact of Brexit and the new regulatory frameworks it has caused to be implemented have created massive upheaval and challenges. As Bosworth et al (2021) have observed, innovation and knowledge spillovers tend to be slower in rural regions. These regions tend to be more reliant on exogenous forces for growth opportunities.…”
Section: Agricultural Innovationmentioning
confidence: 69%
“…Reliant on immigrant labor and overseas markets, the impact of Brexit and the new regulatory frameworks it has caused to be implemented have created massive upheaval and challenges. As Bosworth et al (2021) have observed, innovation and knowledge spillovers tend to be slower in rural regions. These regions tend to be more reliant on exogenous forces for growth opportunities.…”
Section: Agricultural Innovationmentioning
confidence: 69%
“…The main themes of research on China’s county-level digital economies include proposing strategies and policies and interpreting theoretical connotations [ 41 ]. For example, some studies have analyzed strategies or paths for special counties [ 42 , 43 ]. In those studies, digital infrastructure construction, e-commerce economy, and digital finance were regarded as important driving forces for rural digital economy development.…”
Section: Introductionmentioning
confidence: 99%